Linkerd : service mesh for Kubernetes (Packt Publishing, 2021)
Linkerd is a different kind of service mesh that is ultra-light, ultra-simple, ultra-powerful. Linkerd adds security, observability, and reliability to Kubernetes, without the complexity. It’s CNCF-hosted and 100% open source. Linkerd works by installing a set of ultralights, transparent proxies next to each service instance. These proxies automatically handle all traffic to and from the service. Because they’re transparent, these proxies act as highly instrumented out-of-process network stacks, sending telemetry to, and receiving control signals from, the control plane. This design allows Linkerd to measure and manipulate traffic to and from your service without introducing excessive latency. In order to be as small, lightweight, and safe as possible, Linkerd’s proxies are written in Rust and specialized for Linkerd. You can learn more about the proxies in the Linkerd proxy repo. It is a must tool for everyone who is working with microservices especially when working with Kubernetes. By the end of the course, you will be able to understand how Linkerd works and learn to install CLI manually.